PENGEMBANGAN APLIKASI PEMILIHAN SMARTPHONE ANDROID MENGGUNAKAN METODE WEIGHTED PRODUCT BERBASIS ANDROID - Yosef Ricardo Latif, Joko Susilo (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
This research is motivated by the difficult problem of giving recommendation of android smartphone according to user requirement and difficulty determine alternative product like brand, type, and specification criterion for selection of android smartphone. Researchers apply the Weighted Product method in calculating the recommendation of android smartphone. Researchers also apply prototyping method as system development method in this research. Data collection and user needs are done by conducting structured interviews on smartphone reviewers from Getective.com, non-direct observation through internet media and literature studies such as reading books, journals and websites as a supporting reference for this research. Through the process of research that has been done and the application development process that has been going on, the researchers concluded that the Weighted Product method is proven to provide recommendations android smartphone that suits the needs of prospective users and smartphone selection applications that researchers create, proven to facilitate users to get recommendations android smartphone according to their needs.Keywords: Weighted Product, Smartphone, Decision Support System, Android